2018
DOI: 10.1111/jgs.15258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Area‐Level Socioeconomic Deprivation on Risk of Cognitive Dysfunction in Older Adults

Abstract: This analysis combining data from two health systems shows that area deprivation is an independent risk factor for cognitive dysfunction in older adults. Adults living in areas of greatest socioeconomic deprivation may benefit from targeted strategies aimed at improving modifiable risk factors for dementia. Further cross-national analysis investigating the impact of area- level deprivation is needed to address socioeconomic disparities and shape future policy to improve health outcomes in older adults.© 2018 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 47 publications
15
37
0
Order By: Relevance
“…The study involved new analysis of data from the TUDA aging cohort study (ClinicalTrials.gov Identifier: NCT02664584). As described in detail elsewhere, 13 5,186 community-dwelling adults aged ≥60 years were recruited between 2008 and 2012 from two jurisdictions within the island of Ireland -Northern Ireland (United Kingdom, UK) and the Republic of Ireland. The TUDA study initially aimed to investigate the role of nutrition and lifestyle factors in the etiology of common age-related diseases, namely, dementia, osteoporosis and cardiovascular disease.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study involved new analysis of data from the TUDA aging cohort study (ClinicalTrials.gov Identifier: NCT02664584). As described in detail elsewhere, 13 5,186 community-dwelling adults aged ≥60 years were recruited between 2008 and 2012 from two jurisdictions within the island of Ireland -Northern Ireland (United Kingdom, UK) and the Republic of Ireland. The TUDA study initially aimed to investigate the role of nutrition and lifestyle factors in the etiology of common age-related diseases, namely, dementia, osteoporosis and cardiovascular disease.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Socioeconomic status was measured as area-based deprivation by adopting a novel crossjurisdictional appraoch, whereby geo-referenced address-based information was used to map and link participants to official socioeconomic indicators of deprivation within Northern Ireland (UK) and the Republic of Ireland, as previously described in detail. 13…”
Section: General Health Lifestyle and Biophysical Measuresmentioning
confidence: 99%
“…2018) and socio‐economic deprivation (McCann et al . 2018). The VALID project will now build upon these earlier findings from the TUDA cohort, to investigate the potential role of flavan‐3‐ols in helping to prevent cognitive decline and other adverse health outcomes in ageing.…”
Section: The Valid Projectmentioning
confidence: 99%
“…Furthermore, the area in which a person lives can influence health above and beyond that observed for individual socio-economic factors. One recent study showed that older adults living in areas with the greatest socio-economic deprivation, compared with those living in areas of least deprivation, had poorer health profiles, higher disease risk factors and worse cognitive function (12) .…”
Section: Key Factors That Influence Ageing/intrinsic Capacitymentioning
confidence: 99%